The Ornamental Fish Trade: An Introduction with Perspectives for Responsible Aquarium Fish Ownership - E. J. Livengood; Frank A. Chapman (EDIS, 2007)
FA-124, an 8-page illustrated fact sheet by E. J. Livengood and F.A. Chapman, aims inform aquarium owners about the ornamental fish industry so that they can make conscientious decisions about their purchases, and help protect the wild species and safeguard the natural environments. It describes how aquarium fish are collected or cultured, ecological considerations, and things a potential aquarist should know. Includes resource list. Published by the UF Department of Fisheries and Aquatic Sciences, May 2007.